Political Bias against Atheists: Talk Shows Targeting Arabic-Speaking Audiences - Khazaal, Natalie (Religions, 2023)
Atheism has stirred up controversy in the Arabic-speaking world since the 2011 uprisings, when atheists there began appearing in public. What role does Arabic mass media play in the modern politics of minorities such as atheists, given the heated debates that it hosts on atheism? This question is important because perceptions of media frames influence the behavior of politicians and the electorate—and, as a result, laws that affect minority groups such as atheists. This article focuses on Lebanon, where eight of the nine television channels are affiliated with and funded by religious–political parties. It explores the existence of bias against atheists on televised Lebanese talk shows and news reports (2010–2022). Our findings reveal significant bias (69% overall and over 85% in speaker prominence bias), with channels that promote communal religious practice exhibiting the highest levels. Ultimately, our findings demonstrate that television, as the most influential Lebanese and Arabic mass medium, likely affects the public’s negative perceptions of Arabic-speaking atheists. Our findings reflect the decrease in objectivity in conflict-based media and such media’s poor understanding or intentional disregard for media’s crucial role in building a fair, democratic society.